Kulturanalytisk metod: Bidrag till etnologiämnets metoddiskussion - Öhlander, Magnus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
How is cultural analysis practiced? How is empirical data organized and coded? What is an interpretation and what is a good interpretation? With what techniques and with what criteria do we judge the quality of an analysis? Questions like these are of vital importance for cultural analysis. In a Swedish context, this kind of analysis has been criticised for lack of transparency, which consequently makes it difficult to discuss methodology as well as the quality of the analysis. This article is a contribution to the discussion about the methodology of cultural analysis as it is practiced in Swedish Ethnology. It is impossible to speak of one cultural analysis. Each understanding of culture is grounded in a specific theoretical tradition. How analysis is done is then depending on the theoretical frame. Despite these differences it is argued that there are some similarities in every cultural analysis. Similarities are to be found in the techniques and procedures in the everyday practice of research, in the reading and rereading of the material, in the pottering with the and sorting out of empirical finding and in how theory gives suggestions to relevant questions and interpretations. This article is an attempt to a preliminary description of everyday practice of cultural analysis.